2022
DOI: 10.3233/jrs-200038
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of burnout levels among anesthesiologists and anesthesiology technicians in Kosovo: A cross-sectional study

Abstract: BACKGROUND: Anaesthesiology practitioners experience extraordinary pressure and stress in their daily work. OBJECTIVE: The purpose of this research is to assess the occupational factors and burnout syndrome among anaesthesiologists and anaesthesiology technicians in Kosovo. METHODS: This is a cross-sectional study carried out on a sample of 154 (out of 220) anaesthesiologists and anaesthesiology technicians in Kosovo. We collected the data using the Maslach Burnout Inventory and Occupational Role Stressors Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…An Italian study in 2020 assessed burnout among anesthesiologists and intensivists and showed that 79.9% (686) exhibited moderate levels of burnout ( 3 ). A cross-sectional study in Kosovo surveyed 154 anesthesiologists and anesthesia technicians in Kosovo and found that approximately one-third of Kosovar anesthesiologists and anesthesia technicians exhibited high levels of burnout ( 4 ). A U.S. study included 3,898 members of the American Society of Anesthesiologists and showed that 59.2% of the study subjects were at high risk of burnout ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…An Italian study in 2020 assessed burnout among anesthesiologists and intensivists and showed that 79.9% (686) exhibited moderate levels of burnout ( 3 ). A cross-sectional study in Kosovo surveyed 154 anesthesiologists and anesthesia technicians in Kosovo and found that approximately one-third of Kosovar anesthesiologists and anesthesia technicians exhibited high levels of burnout ( 4 ). A U.S. study included 3,898 members of the American Society of Anesthesiologists and showed that 59.2% of the study subjects were at high risk of burnout ( 5 ).…”
Section: Introductionmentioning
confidence: 99%